2017
DOI: 10.1093/femsle/fnx159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the contaminant bacterial communities in sugarcane first-generation industrial ethanol production

Abstract: The industrial ethanolic fermentation process is operated in distilleries, either in fed-batch or continuous mode. A consequence of the large industrial ethanol production is bacterial contamination in the fermentation tanks, which is responsible for significant economic losses. To investigate this community, we accessed the profile of bacterial contaminant from two distilleries in Brazil, each operating a different fermentation mode, throughout sugarcane harvest of 2013-2014. Bacterial communities were access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
4
9
0
5
Order By: Relevance
“…The sequences rated as Weissella almost disappeared after the Heater steps (Figure 3). A recent study found lower abundances of Weissella in fermentation tanks,[8] as recorded in this study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The sequences rated as Weissella almost disappeared after the Heater steps (Figure 3). A recent study found lower abundances of Weissella in fermentation tanks,[8] as recorded in this study.…”
Section: Discussionsupporting
confidence: 77%
“…Consequently, high costs in clean up the equipment arise, reducing the productivity in ethanol production [46]. The main contaminant taxon is a Lactobacillus , specifically a Lactic Acid Bacteria (LAB) found in high proportion during the fermentation procedure [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de certa individualidade de cada processo de produção de etanol e uso de diferentes matérias primas, como milho e cana-de-açúcar, todos trabalhos evidenciaram que os microrganismos contaminantes prevalentes sempre são bactérias ácido lácticas, particularmente do gênero Lactobacillus, representando mais de 40% dos isolados (SKINNER; LEATHERS, 2004;BONATELLI et al, 2017).…”
Section: Figuraunclassified
“…A grande maioria das bactérias contaminantes de fermentações etanólicas de primeira geração no Brasil são LAB, sendo que entre as espécies mais abundantes destacam-se L. fermentum e L. plantarum (CARVALHO-NETTO et al, 2015;BONATELLI, 2017). Acredita-se que a capacidade de tolerar altas concentrações de etanol e baixos índices de pH sejam algumas das explicações da presença destes microrganismos em fermentações industriais brasileiras (AMORIM et al, 2011).…”
Section: Bactérias Lácticas De Lactobacillusunclassified
“…Contudo, a aplicação indiscriminada destas práticas envolve um grande aporte de recursos e pode gerar problemas graves para a indústria, espécie humana e meio ambiente (LUDWIG, OLIVA-NETO & ANGELIS, 2001). Carvalho-Netto et al (2015) e Bonatelli et al (2017) mostram que bactérias lácticas e acéticas estão entre os microrganismos mais abundantes do sistema, sendo uma das principais causadoras das perdas de produtividade e geração de estresses bióticos.…”
Section: Introductionunclassified